1988
DOI: 10.2151/jmsj1965.66.6_841
|View full text |Cite
|
Sign up to set email alerts
|

Supercooled Cloud Tunnel Studies on the Growth of Snow Crystals between-4 and-20°C

Abstract: Snow crystal growth in free fall by vapor diffusion under water saturation and riming was studied up to 30 min in a supercooled cloud tunnel. The results showed that: 1) the growth rates were pronouncedly highest along a-axis at -15* and along c-axis at -5.5*.Each peak coincided with the growth of dendrites and needles, respectively; 2) polycrystalline snows, consisting of spatial dendrites and spatial plates, were observed very frequently below-15°C;3) the variation of fall velocity with growth time could be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
70
0

Year Published

1989
1989
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(76 citation statements)
references
References 16 publications
6
70
0
Order By: Relevance
“…The 10-min duration is less than our earlier studies (Takahashi and Fukuta 1988;Takahashi et al 1991), but the longer growth times produce greater amounts of riming, more cases with spatial branches, and greater chances of drifting into the wall. Despite the shorter growth time, the stellar and dendrite crystals nevertheless have sizes typical of crystals in nature.…”
Section: Methodsmentioning
confidence: 53%
See 2 more Smart Citations
“…The 10-min duration is less than our earlier studies (Takahashi and Fukuta 1988;Takahashi et al 1991), but the longer growth times produce greater amounts of riming, more cases with spatial branches, and greater chances of drifting into the wall. Despite the shorter growth time, the stellar and dendrite crystals nevertheless have sizes typical of crystals in nature.…”
Section: Methodsmentioning
confidence: 53%
“…The vertical supercooled cloud tunnel used here is the same as that in Takahashi et al (1991). In the tunnel, a snow crystal can be suspended freely and grown in a vertical stream of artificially generated supercooled cloud by applying aerodynamic mechanisms for horizontal stability and by continuously adjusting the upward wind speed to match that of the (generally increasing) crystal fall speed.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, a lack of observations in mixed-phase clouds (resulting from the challenge of detecting layers of supercooled liquid water in the ice-dominated parts of clouds) impeded an accurate computation of the liquid water content (LWC)-to-IWC ratio, which therefore limits an understanding of phase partitioning (Kalesse et al, 2016). Wind tunnel experiments by Takahashi and Fukuta (1988) and Fukuta and Takahashi (1999) measured the riming enhancement as an increase in ice particle fall speed (V ). They also showed that riming has a peak at −10.5 • C for low LWCs, where ice particles are isometric, and therefore have higher V .…”
Section: Characteristics Of Rimingmentioning
confidence: 99%
“…Circles and triangles indicate graupel embryos and graupel particles, respectively. Takahashi and Fukuta (1988), even isometric crystals such as columns and thick plates initiated at temperatures of @À10 C, which are considered the most promising candidate of graupel embryos, would grow in 10 minutes into densely rimed snow particles of 0.3 mm. The terminal fall velocity of the densely rimed snow particles would be @35 cm s À1 and the falling distance for ten minutes after the ice initiation would be, at most, 100 m and negligibly small.…”
Section: Discussionmentioning
confidence: 99%